2000
DOI: 10.1111/j.1460-2466.2000.tb02866.x
|View full text |Cite
|
Sign up to set email alerts
|

Media Bias in Presidential Elections: A Meta-Analysis

Abstract: A meta-analysis considered 59 quantitative studies containing data concerned with partisan media bias in presidential election campaigns since 1948. Types of bias considered were gatekeeping bias, which is the preference for selecting stories from one party or the other; coverage bias, which considers the relative amounts of coverage each party receives; and statement bias, which focuses on the favorability of coverage toward one party or the other. On the whole, no significant biases were found for the newspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(96 citation statements)
references
References 60 publications
0
91
0
5
Order By: Relevance
“…Based on media bias model and capitalistic political economy theory, the traditional media have been found to be creating and/or reinforcing democratic malaise and political apathy (D'Alessio & Allen, 2000;Luengo & Coimbra-Mesquita, 2013;Herman & Chomsky, 2002). The advent of digital media technologies, with democratising features, has, however, provided a ray of hope that citizens' civic interests would be reawakened.…”
Section: Discussionmentioning
confidence: 99%
“…Based on media bias model and capitalistic political economy theory, the traditional media have been found to be creating and/or reinforcing democratic malaise and political apathy (D'Alessio & Allen, 2000;Luengo & Coimbra-Mesquita, 2013;Herman & Chomsky, 2002). The advent of digital media technologies, with democratising features, has, however, provided a ray of hope that citizens' civic interests would be reawakened.…”
Section: Discussionmentioning
confidence: 99%
“…Í því sambandi er fyrirbaerið fjandsamleg fjölmiðlun (e. "hostile media phenomenon) talsvert rannsakað. Í því felst að fjölmiðlaumfjöllun sem af óvilhöllum aðila er talin nokkuð hlutlaus er skynjuð sem hlutdraeg og talin draga taum pólitískra andstaeðinga af þeim sem hafa pólitíska skoðun eða stefnu tengda viðkomandi máli (Vallone et al 1985;D'Alessio & Allen, 2000 ). Vissulega getur verið erfitt að ákveða með vissu hvort upplifun á pólitískri fréttaslagsíðu stafar af því að slagsíðan er raunveruleg, eða hvort aðrir þaettir sem tengjast pólitískri afstöðu skipta meira máli.…”
Section: Frá Flokksmiðlun Til Pólitískrar Markaðsfjölmiðlunarunclassified
“…Ample political communication research has addressed media neutrality and bias [61,62]. Scholars have not only supported the notion of a media bias, but also asserted that mass media has a liberal bias [63]; whereas, other scholars believe that there is a conservative bent controlled by corporate interests [64].…”
Section: Political News Consumption and Media Trust And Performancementioning
confidence: 99%
“…Baby Boomers' vote choice was equally divided between the candidates (50% for Obama versus 49% for McCain) [31]. Similarly, a 2012 study found that 60% of Millennials voted for Obama, compared to 47% of Boomers (age [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] [33]. Moreover, Boomers are more politically involved than Millennials.…”
Section: Introductionmentioning
confidence: 99%